Love and Duty Confederate Widows and the Emotional Politics of Loss - Elder, Angela Esco (Book collections on Project MUSE., 2022)
"Between 1861 and 1865, approximately 200,000 women were widowed by the deaths of Civil War soldiers. They recorded their experiences in diaries, letters, scrapbooks, and pension applications. In Love and Duty, Angela Esco Elder draws on these materials--as well as songs, literary works, and material objects like mourning gowns--to explore white Confederate widows' stories, examining the records of their courtships, marriages, loves, and losses to understand their complicated relationship with the Confederate state. Elder shows how, in losing their husbands, many women acquired significant cultural capital, which positioned them as unlikely actors to gain political influence"--